2004
DOI: 10.1121/1.1810238
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of spatial average equalization: A statistical reverberation model approach

Abstract: Traditionally, multiple listener room equalization is performed to improve sound quality at all listeners, during audio playback, in a multiple listener environment (e.g., movie theaters, automobiles, etc.). A typical way of doing multiple listener equalization is through spatial averaging, where the room responses are averaged spatially between positions and an inverse equalization filter is found from the spatially averaged result. However, the equalization performance, will be affected if there is a mismatc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The advantages of this filter-bank include straightforward implementation of fractional oversampling and computationally efficient implementations [29]. Within the framework of the GDFT filter-bank, the analysis filters, , are calculated from a single prototype filter, , with bandwidth according to the relation [29] ( 15) where the properties of the frequency and time offset terms, and , are discussed in, for example, [29]. We set these to and as in [31].…”
Section: A Oversampled Filter-banksmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of this filter-bank include straightforward implementation of fractional oversampling and computationally efficient implementations [29]. Within the framework of the GDFT filter-bank, the analysis filters, , are calculated from a single prototype filter, , with bandwidth according to the relation [29] ( 15) where the properties of the frequency and time offset terms, and , are discussed in, for example, [29]. We set these to and as in [31].…”
Section: A Oversampled Filter-banksmentioning
confidence: 99%
“…Bharitkar et al [15] use spatially averaged RTFs for the design of the equalization filter. In [16], the authors modify the desired signal in the multichannel inverse filter design, such that the late reverberation is equalized while the early reflections are preserved.…”
mentioning
confidence: 99%
“…However, it has been observed that exact equalization is of limited value in practice, when the RTF estimates contains even moderate errors [1,3,9]. Various alternatives have been proposed for improving robustness to RTF inaccuracies [10,11,12].…”
Section: Gm(z) Satisfyingmentioning
confidence: 99%
“…However, if the ATFs are time-varying, the deconvolution performance is greatly degraded even if the variation is quite small [7]. Sensitivity to small fluctuations due to a temperature change or to a small change in the speaker/microphone position can be improved by using a robust technique to estimate the ATFs, e.g., reducing the filter energy [8], spatial averaging [9], or pseudo-inverse calculation [10]. However, under large-fluctuations due to movement of the speaker's head, movement of the surrounding people, and obstacles located between the microphones and the speaker, the dereverberation performance of the MIF-based techniques is upper-limited.…”
Section: Introductionmentioning
confidence: 98%